Pertanggungjawaban Notaris atas Akta yang Memuat Unsur Tindak Pidana Pemalsuan dalam Perspektif Hukum Positif di Indonesia. - Diana Ayu Mardiani (Jurnal Hukum Lex Generalis, 2025)
This study aims to analyze the notary’s liability for the contents of deeds containing elements of criminal forgery and to examine the legal provisions violated along with the application of criminal, civil, and administrative sanctions from a normative perspective. The research method employed is normative juridical legal research, focusing on the study of relevant statutory regulations, court decisions, legal doctrines, and principles of law. The results indicate that a notary’s involvement in drafting a deed containing false statements may fulfill the elements stipulated in Articles 263 and 264 of the Indonesian Criminal Code (KUHP), Article 1365 of the Indonesian Civil Code (KUHPerdata), and Articles 16 and 84 of the Notary Office Law (UUJN). Such violations result in cumulative legal liability, encompassing criminal, civil, and administrative consequences. The application of the legal certainty theory and legal liability theory underscores that strict and consistent sanctions are essential to uphold the integrity of the notarial profession and restore public trust in the legal system. A case study of Supreme Court Decision No. 1096 K/Pid/2006 demonstrates that the application of cumulative sanctions is effective in deterring misconduct while reinforcing the function of law as an instrument of protection and legal certainty.